Metodologia badań nad lękiem językowym - Piechurska-Kuciel, Ewa (Neofilolog, 2009)
The paper aims at analysing the methodological perspectives applied in studies on language anxiety. First, the sample selection procedures and characteristics are presented, followed by the analysis the main research tools applied in this area, and by the outline of the most popular research designs and the description of basic data analyses. The paper finishes with an attempt to depict methodological research perspectives concerning further investigations of language anxiety.